Investment in information technology and its impact on sustainable development with reference to Malaysia - Saad Hassan Ali; Yassin Abed Salh; Jabbar Sakban Hamid (Journal of Madenat Alelem University College, 2022)
Information and communication technology (ICT) is considered as the main pillar of the Digital Economy; and it represents all the hardware and software of computers as well as networks and all the required equipment to process, save, organize, show, send and recall information.ICT provides a unique platform to host a large number of sustainable development services, such as E-commerce, mobile payment systems, E-learning applications, E-health, earth observation services and climate change, and even more E-government. Therefore, investment in such technologies would help to ensure finding solutions to meet the challenges of sustainable development. This research fosters the need of investment & use of ICTs as an enabler of sustainable development. Some experiments on investment & use of ICTs for different purposes in Malaysia reviewed and conclusions drawn on how it does support the sustainable development, which may be similar and bear lessons for many developing countries